Nilai-Nilai Edukatif Dari Peringatan Rebokasan Menurut Kajian Ilmu Pendidikan Islam - Raito, Raito; Masruroh, Imas (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
Muslims in Indonesia represent one of the largest Islamic communities in the world, providing a concrete example of how Islamic principles are practiced within a culturally pluralistic society. This diverse cultural backdrop influences the way Islamic teachings are understood and applied. Among many Indonesian Muslims, there remains a strong adherence to ritualistic practices, one of which is the celebration of Rebokasan. Rebokasan is a phenomenon rooted in the intensive cultural assimilation of Javanese traditions with Islam. The objectives of this study are to: (1) Understand the meaning of Islamic Education; (2) Identify the educational values inherent in the Rebokasan celebration; (3) Examine the educational values of Rebokasan through the lens of Islamic Education studies. This research employs a library research approach with descriptive analytical methods, drawing on primary sources (Qur'an and Hadith) and secondary sources (supportive books). Data collection techniques include documentation, qualitative analysis, and content analysis within the framework of Islamic Education studies. The findings reveal four educational values embedded in the Rebokasan celebration: First, the Value of Strengthening Faith (Aqidah), as the community engages in collective prayers during Rebokasan. Second, the Value of Social Concern, demonstrated by the sharing of food among community members. Third, the Value of Maintaining Social Bonds (Silaturahmi), expressed through community gatherings in mosques for the Rebokasan festivities. Fourth, the Value of Cultural Cooperation (Gotong Royong), evident in the communal effort to prepare and distribute food as an act of charity. Keywords: Islamic Education, Educational Values, Rebokasan